Unveiling Muhammadiyah's Cultural Da'wah: An Ethnographic Exploration at PCM Kasihan, Yogyakarta - Ahmad Rifai; Rovi Husnaini; Dikdik Dahlan Lukman; Aris Hassama (UIN Sunan Gunung Djati Bandung, 2026)
This ethnographic study examines Muhammadiyah's grassroots cultural da'wah via PCM Kasihan, Bantul, Yogyakarta (2023–2024), revealing how this puritanical movement negotiates and transforms Javanese culture. Grounded in cultural da'wah, Dahlanism (selective-accommodative-transformative strategy of K.H. Ahmad Dahlan), and purification-accommodation dialectics (Geertz, Malinowski), it deploys participant observation, interviews, FGDs, and thematic analysis of da'wah interactions. Findings highlight Dahlanism's success: accommodating Javanese calendars/Krama in rituals; repurposing yasinan/tahlilan for Qur'anic education; maslahah-driven cultural partnership. Challenges include balancing purity with tradition and cadre hesitancy; recommendations advocate integrating the model into central training and inter-branch forums. Contributions: empirical micro-portrait of da'wah; theoretical sharpening of Dahlanism beyond puritan-traditional binaries for modern Islamic locality strategies.